Usability testing of existing type 2 diabetes mellitus websites. (August 2016) - Davis, Dorian; Jiang, Steven
Highlights: A usability evaluation was conducted for the American Diabetes Association, WebMD and National Diabetes Education websites. Results show that all participants experienced information overload for all three websites. Design solutions to decrease information overload were proposed. Abstract: Background: Given the significant increase in the use of the internet as an educational tool for diabetes, very little research has been published on the usability of healthcare websites, even though it is a determining factor for user satisfaction. Objective: The aim of this study is to evaluate and critique the interfaces of existing diabetes websites for usability concerns and provide design solutions for improvement. Emphasis is placed on Type 2 Diabetes Mellitus since it is the most common and life threatening form of diabetes. Method: A usability test was performed on the interfaces of three existing diabetes websites, American Diabetes Association (www.diabetes.org ), WebMD (www.webmd.com ) and the National Diabetes Education Program (ndep.nih.gov ). The goal was to collect qualitative and quantitative data to determine: (1) if participants are able to complete specified tasks successfully; (2) the length of time it takes participants to complete the specified tasks and; (3) participants' satisfaction with the three websites. Twenty adults, 18 years of age and older participated in the study. Results: The results from the MANOVA test revealed a significant difference between the three websites for number of clicks, number of errors and completion time when analyzed simultaneously. The ANOVA tests revealed a significant difference for all three variables. The Student-Newman-Keuls (SNK) test shows a significant difference for completion time between American Diabetes Association and WebMD. A significant difference was found for the number of clicks for the National Diabetes Education Program compared to the American Diabetes Association and WebMD. However, no significant difference was found for the number of clicks between American Diabetes Association and WebMD. Lastly, a significant difference was found between each interface for number of errors. Discussion: Although, the American Diabetes Association web-interface was most favorable, there were many positive design elements for each interface. On the other hand, the significant amount of information overload experienced for each website left participants feeling perplexed. Thus, innovative solutions are needed to reduce information overload and ensure users are engaged and empowered to make informed decisions about their healthcare.